The Effect of Corn Flour Substitution on Moisture Content and Organoleptic Properties in Cookies (Zea Mays L) - Titik Harianti; Ruksanan Ruksanan; Hastian Hastian; La Oge; Rustan Ari (Journal of Agriculture, Agribusiness, Welfare, Technology, Humanity, Environment, Social, and Economy, 2026)
This study aimed to determine the effect of corn flour (Zea mays L.) substitution on the moisture content and organoleptic characteristics of cookies, including color, aroma, texture, and taste. The study employed an experimental method with a quantitative approach using a Completely Randomized Design (CRD) consisting of four treatments: A0 (0%), A01 (15%), A02 (25%), and A03 (35%), each with three replicates, resulting in 12 experimental units. The cookie production process involved substituting corn flour for wheat flour; moisture content was then analyzed using the oven method, and organoleptic testing was conducted with 15 panelists using a 1–5 hedonic scale. The results indicated that corn flour substitution influenced the moisture content and organoleptic characteristics of the cookies. The highest moisture content was obtained in treatment A0 at 4.56%, while the lowest moisture content was found in treatment A01 at 2.46%. The organoleptic test results showed that treatment A02 received the highest score for color at 3.80, while the highest scores for aroma, texture, and taste were obtained in treatment A0 at 4.00, 3.93, and 4.00, respectively. In general, increasing corn flour substitution caused the color to change to a more yellowish-brown and made the cookies more brittle due to the absence of gluten in corn flour. Based on all test parameters, treatment A02 with 25% corn flour substitution showed the most balanced results and was still acceptable to the panelists. This study indicates that corn flour has the potential to be used as a wheat flour substitute in the development of cookies based on local food ingredients.